PENGEMBANGAN ASESMEN UNTUK MENGUKUR PEMAHAMAN KONSEP FISIKA SISWA SMA - WERDHIANA, I Komang (2009)
This study is aimed at developing an assessment instrument for measuring high school students understanding of physics concept. A conceptual understanding test was developed to measure student understanding of the concept, and a mathematical approach test was also developed to measure the student ability to solve calculating or arithmetic problems and constructed on the basis of the conceptual understanding test, each problem of the conceptual understanding test was changed into calculating problems. Content validation involved an expert judgment, while test tryout involved senior high school student in Bandung. First tryout which was conducted on 354 students resulted in two valid and reliable test sets of 28 test items each. These two sets of test were then tested on 605 students. It was found that scores of the two sets of test are significantly different. Students who are able to solve problems in the mathematical approach test correctly, are might be, able to solve those of conceptual understanding test correctly. In contrary, the students who are able to solve the problems in the conceptual understanding test correctly will be able to answer the question of mathematical approach test correctly. Gender disparity is not significant in solving calculation questions as well as answering conceptual understanding questions on dynamic electric. The result of analyses were based on the students' choice of answer and the reasons given by them. A finding shows that most student have a conceptual difficulty understanding electric current. The conceptual understanding test can measure the students' understanding of dynamic electrics concept, and motivated the students to understand the physics concept properly. Hence, the assessment in use should emphasize the understanding of concept.